2022
DOI: 10.29303/jpm.v17i4.3671
|View full text |Cite
|
Sign up to set email alerts
|

Development of problem-solving based test instruments to foster the students creative thinking skills on environmental conservation

Abstract: This study aims to obtain data on the feasibility of problem-solving-based test instruments to foster the creative thinking skills of junior high school students on environmental conservation. The method used in this study is Research & Development (R&D) with development procedures according to Sugiyono. This study was conducted in 5 stages: potentials and problems, data collection, product design, design validation, and design revision. The instrument used in this development research is a question va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…61.5% of respondents stated that students are more interested in adventure games for learning activities. Adventure games are software programs that present a mock environment where players will interact to solve problems in the game [44]. Adventure games have different levels of difficulty in each level.…”
Section: Resultsmentioning
confidence: 99%
“…61.5% of respondents stated that students are more interested in adventure games for learning activities. Adventure games are software programs that present a mock environment where players will interact to solve problems in the game [44]. Adventure games have different levels of difficulty in each level.…”
Section: Resultsmentioning
confidence: 99%
“…The issues revealed that students' critical thinking still needs to be improved. It is evident in the aptitude of students who struggle with problem-solving ability [5]. Students struggle to argue and communicate their viewpoints clearly, even during class discussions.…”
Section: Introductionmentioning
confidence: 99%